1964
DOI: 10.1021/bi00894a009
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonyl Fluorides as Inhibitors of Esterases. II. Formation and Reactions of Phenylmethanesulfonyl α-Chymotrypsin*

Abstract: Phenylmethanesulfonyl fluoride reacts stoichiometrically with a-chymotrypsin, producing an inactive monosulfonyl enzyme and one equivalent of free acid. Titration of the enzyme with the inhibitor results in nearly complete inactivation when the equivalent amount of inhibitor is present, and treatment of enzyme with a large excess of [7-14C]phenylmethanesulfonyl fluoride leads to incorporation of the expected amount of l4C. Irreversibly inhibited chymotrypsin and chymotrypsinogen do not react significantly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0
1

Year Published

1970
1970
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(122 citation statements)
references
References 27 publications
8
113
0
1
Order By: Relevance
“…The presence of the serine consensus motif in the esterase confirmed that this enzyme is a typical serine hydrolase which performs hydrolysis of ester bonds after nucleophilic attack of the hydroxyl group from the active serine residue. Studies of inhibition by PMSF, a serinehydrolase inhibitor (Gold & Fahrney, 1964;Kraut, 1977), further support the involvement of the active serine in the catalytic mechanism of the esterase (unpublished results).…”
Section: Discussionmentioning
confidence: 78%
“…The presence of the serine consensus motif in the esterase confirmed that this enzyme is a typical serine hydrolase which performs hydrolysis of ester bonds after nucleophilic attack of the hydroxyl group from the active serine residue. Studies of inhibition by PMSF, a serinehydrolase inhibitor (Gold & Fahrney, 1964;Kraut, 1977), further support the involvement of the active serine in the catalytic mechanism of the esterase (unpublished results).…”
Section: Discussionmentioning
confidence: 78%
“…Diisopropyl fluorophosphate and phenylmethylsulfonyl fluoride, which irreversibly and specifically react with active site serine residues (32,33), partially inhibited protease IV activity. TLCK totally abolished the activity of protease IV, suggesting the presence of a histidine residue in the active site of the enzyme (34).…”
Section: Resultsmentioning
confidence: 99%
“…Kinetics of Inhibition-The inactivation of PPT1 was assumed to proceed via formation of an intermediate Michaelis complex as described previously (11). The reaction is assumed to follow the course shown in Equation 1.…”
Section: Methodsmentioning
confidence: 99%